The The Representation of Anger in The Main Character of The Watcher Series - Nurahmah, Gita Indah; Hellystia, Devi (JADEs Journal of Academia in English Education, 2023)
The majority of this research was verbal anger which occurred most frequently. It can be seen in the main character more often using high tones and speaking harshly in speaking. This proves that anger that comes from feeling threatened tends to trigger angry emotions. This is followed by another finding which amounted to the second most in this finding is the uncontrol type of anger impulsivity. The third is the externalization type of anger locus. Then the reflection type of anger direction, and the punitive of anger objective. This research aims to discover the types of anger and analyze the causes of anger represented in the dialogue of the main character in the TV series The Watcher. This research used a qualitative descriptive method, to classify, and analyze data. The data of this research were the dialogue representation of anger in The Watcher series. The representation of anger in the dialogue with the main character was analyzed using Fernandez's six dimensions.